2017
DOI: 10.4082/kjfm.2017.38.6.358
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis Affects Health-Related Quality of Life in Korean Adults with Chronic Diseases: The Korea National Health and Nutritional Examination Surveys 2009–2013

Abstract: BackgroundOsteoarthritis (OA) is a chronic disease that commonly afflicts the elderly. This disease reduces the health-related quality of life (HRQoL) and causes a significant social burden. Whether the effect of coexisting chronic conditions on HRQoL varies according to the presence of OA remains unclear. Therefore, this study aimed to investigate this notion.MethodsA total of 13,395 participants were identified from the 2009–2013 Korean National Health and Nutrition Examination Survey for analysis. HRQoL was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This registry collects data from many hospitals and surgeons, and captures virtually all hip and knee operations performed within the region and approximately 75% of those undertaken in Manitoba (Singh et al, 2016). Osteoarthritis is a chronic condition that may lead to joint failure and disability, adversely affecting HRQoL (Public Health Agency of Canada, 2010;Yang et al, 2017). The aging of the population is driving the increasing prevalence of osteoarthritis and this trend is projected to continue (Birtwhistle et al, 2015;Woolf, 2015).…”
Section: Preface To Chaptermentioning
confidence: 99%
“…This registry collects data from many hospitals and surgeons, and captures virtually all hip and knee operations performed within the region and approximately 75% of those undertaken in Manitoba (Singh et al, 2016). Osteoarthritis is a chronic condition that may lead to joint failure and disability, adversely affecting HRQoL (Public Health Agency of Canada, 2010;Yang et al, 2017). The aging of the population is driving the increasing prevalence of osteoarthritis and this trend is projected to continue (Birtwhistle et al, 2015;Woolf, 2015).…”
Section: Preface To Chaptermentioning
confidence: 99%
“…In previous researches, pain, physical disabilities, decreased mobility (function), and mental health status due to OA have been proven to decrease HRQol of OA patients [24][25][26]. Especially, Yang et al reported that HRQoL, evaluated with the EQ-5D index, could be affected more negatively by OA in Korean elderly participants in 2017 [27]. In this research, it was demonstrated that OA could affect HRQoL using EQ-5D in middle aged female participants controlling for socio-economic factors and health behaviour-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…OA is a degenerative disease accompanied with progressive cartilage degradation. Aging is one of the most significant risk factors in OA [ 1 , 2 ]. Although the mechanisms underlies OA awaits to be fully understood, the cartilage integrity is believed to be affected by inflammatory cytokines and matrix remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis (OA) is one of the most common chronic diseases among aged population [ 1 , 2 ]. Various factors, for example, abnormal joint development, joint injury, overweight, inherent factor and aging, contribute to the pathophysiology of OA [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%